1990
DOI: 10.1002/mcs.1220020206
|View full text |Cite
|
Sign up to set email alerts
|

Extended path length UV absorbance detector for capillary zone electrophoresis

Abstract: Abstract. A method of UV absorbance detection for use in capillaries using axial as opposed to transcolumn illumination is described in which laser-induced fluorescence acts as a tool for determining, indirectly, the absorbance within a given length of the capillary. The length of the optical path can be chosen arbitrarily, regardless of the capillary diameter. The technique is demonstrated by means of capillary zone electrophoresis (CZE), in which path lengths of up to a few millimeters can be tolerated witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 9 publications
0
5
1
1
Order By: Relevance
“…A simple comparison of peak areas obtained for the 0.05 mm i.d. on-column longitudinal cell, and the 3.6 mm longitudinal flowthrough cell indicates the significant improvement in responses for all analytes when using There is a disagreement between calculations of the maximum tolerable path length value proposed by Grant and Steuer [12] and our practical findings. Our data show that even a 4.02 mm U-shaped cell path length does not lose more than 31 percent of its effectiveness.…”
Section: Resultscontrasting
confidence: 68%
“…A simple comparison of peak areas obtained for the 0.05 mm i.d. on-column longitudinal cell, and the 3.6 mm longitudinal flowthrough cell indicates the significant improvement in responses for all analytes when using There is a disagreement between calculations of the maximum tolerable path length value proposed by Grant and Steuer [12] and our practical findings. Our data show that even a 4.02 mm U-shaped cell path length does not lose more than 31 percent of its effectiveness.…”
Section: Resultscontrasting
confidence: 68%
“…Various capillary cells (Z-shaped [I 171; extended pathlength [118]; multi-reflectance cells [119]; focussing lenses [120]) have all been used to optimise detection. Zare et al [121] increased the optical pathlength for UV detection by using rectangular capillaries equipped with a specialised injection system [122].…”
Section: Detection Methods For Cementioning
confidence: 99%
“…Mass limits of detection were a factor of 180 lower than those of UV absorbance detectors. Grant and Steuer employed axial illumination with indirect fluorescence detection to determine the absorbance within a given length of capillary (281). Although the authors reported a considerable increase in absorbance signal compared with the usual transcolumn UV absorption technique, tneir results…”
Section: Wang Et Al Employed a Multireflection Absorption Cell Tomentioning
confidence: 99%